2008
DOI: 10.1104/pp.108.116269
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Network of MicroRNA399 andPHO2by Systemic Signaling    

Abstract: Recently, we showed that microRNA399s (miR399s) control inorganic phosphate (Pi) homeostasis by regulating the expression of PHO2 encoding a ubiquitin-conjugating E2 enzyme 24. Arabidopsis (Arabidopsis thaliana) plants overexpressing miR399 or the pho2 mutant overaccumulate Pi in shoots. The association of Pi translocation and coexpression of miR399s and PHO2 in vascular tissues suggests their involvement in long-distance signaling. In this study, we used reciprocal grafting between wild-type and miR399-overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
341
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 411 publications
(375 citation statements)
references
References 56 publications
(91 reference statements)
19
341
1
Order By: Relevance
“…Moreover, transcription factors such as PHR1 (OsPHR1, OsPHR2, PvPHR1, ZmPHR1, TaPHR1), PTF1 (OsPTF1, ZmPTF1), MYB2P-1 (OsMYB2P1), MYB62, WRKY (WRKY75, WRKY6), bHLH32 and ZAT6 are involved in the signalling network to regulate plant adaptation to P stress (Yi et al, 2005;Devaiah et al, 2007a, b;Chen et al, 2007;Valdes-Lopez et al, 2008;Zhou et al, 2008;Devaiah et al, 2009;Chen et al, 2009;Li et al, 2011;Dai et al, 2012;Wang et al, 2013). The posttranscriptional regulation as well as long-distance signal is carried out by microRNAs, for instance miR399 maintain P homeostasis by regulating P transporter PHO2 (Bari et al, 2006;Aung et al, 2006;Lin et al, 2008;Pant et al, 2008). Although the molecular components of P stress signalling in plants has been identified, the overall pathway is still poorly understood and requires further investigation.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Moreover, transcription factors such as PHR1 (OsPHR1, OsPHR2, PvPHR1, ZmPHR1, TaPHR1), PTF1 (OsPTF1, ZmPTF1), MYB2P-1 (OsMYB2P1), MYB62, WRKY (WRKY75, WRKY6), bHLH32 and ZAT6 are involved in the signalling network to regulate plant adaptation to P stress (Yi et al, 2005;Devaiah et al, 2007a, b;Chen et al, 2007;Valdes-Lopez et al, 2008;Zhou et al, 2008;Devaiah et al, 2009;Chen et al, 2009;Li et al, 2011;Dai et al, 2012;Wang et al, 2013). The posttranscriptional regulation as well as long-distance signal is carried out by microRNAs, for instance miR399 maintain P homeostasis by regulating P transporter PHO2 (Bari et al, 2006;Aung et al, 2006;Lin et al, 2008;Pant et al, 2008). Although the molecular components of P stress signalling in plants has been identified, the overall pathway is still poorly understood and requires further investigation.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The miR399 generated in shoots after the onset of P i starvation serves as a long-distance signal to activate P i transport systems by suppressing PHO2 expression in roots (Lin et al, 2008;Pant et al, 2008). Our results obtained in split-root experiments indicate that CAX1 and CAX3 do not mediate the generation and movement of systemic suppressors from the +P i root half to the 2P i root half.…”
Section: Loss Of Function Of Cax1 and Cax3 Disturbs The Regulation Ofmentioning
confidence: 65%
“…In accordance with the inverse correlation between miR399 and PHO2 mRNA levels, transgenic plants overexpressing miR399 phenocopied the pho2 mutant and PHO2 T-DNA knockout lines Chiou et al, 2006). Reciprocal micrografting experiments further demonstrated that a pho2 root genotype is sufficient and necessary for P i accumulation in the shoot, whereas the shoot-to-root movement of mature miR399 is responsible for the degradation of PHO2 mRNA in roots (Bari et al, 2006;Lin et al, 2008;Pant et al, 2008). Moreover, upregulation of miR399 by P i deprivation is mediated by the PHOSPHATE STARVATION RESPONSE1 (PHR1) transcription factor, a key positive regulator of multiple P i starvation-induced (PSi) genes (Rubio et al, 2001;Bari et al, 2006).…”
mentioning
confidence: 64%
See 2 more Smart Citations